The Effect of Digital Marketing, Product Innovation and Social Capital in Increasing Marketing Performance of MSME - Iswahyu Pranawukir; Maria Jashinta Elisabet Hamboer; Alamsyah Alamsyah (Program Studi Manajemen, Fakultas Ekonomi, IBI-K57, 2023)
This study aims to analyze the influence of Digital Marketing, Product Innovation and Social Capital, on the Success of Improving Marketing Performance (Studies on SMEs in South Sumatra). The sampling technique used is non-probability sampling with quota sampling. In this study, a sample of 100 respondents was obtained with the criteria of beneficiaries of UMKM in South Sumatra. The data collection technique uses a questionnaire with a measuring instrument in the form of a Likert scale. The variables contained in this study are the dependent and independent variables. The data used is primary data with quantitative research methods. The data analysis used was multiple linear regression analysis with the help of SPSS. This study shows the results that the significance value of the social capital variable on marketing performance is 0.653 > 0.05 and the value of ???? ℎ ???????????????????? < ???????????????????????? is 0.451 < 1.985. Based on these results, H0 is accepted and H1 is rejected, which means that social capital has no effect on the marketing performance of MSMEs in South Sumatra. The results of the significance of the Digital Marketing variable on marketing performance are 0.101 > 0.05 and the value of ???? ℎ ???????????????????? < ???????????????????????? is 1.654 < 1.985. Based on these results, H0 is accepted and H2 is rejected, which means that Digital Marketing has no effect on the Marketing Performance of MSMEs in South Sumatra. Based on these results, H0 is rejected and H3 is accepted, which means that product innovation has a significant effect on the marketing performance of MSMEs in South Sumatra so that the higher the product innovation that is owned, the higher the resulting marketing performance.